INFLUENCE OF VARIATIONS OF THE CONDUCTIVITY OF UPPER LAYER OF TWO-LAYER SAMPLE ON OF PHASE INTRODUCED ELECTROMOTIVE FORCE OF SUPERIMPOSED TRANSDUCER OF EDDY CURRENT THICKNESS METER - A. V. Chernyshev (Приборы и методы измерений, 2017)
In carrying out eddy current thickness measurement of two-layer conductive objects one from the interfering factors is the presence of variations in the value of the electrical conductivity of the material of the upper layer (coating) when moving from point to point on the surface of object of control or when passing from one object of control to another. The aim of this work is to evaluate the accuracy of determining the thickness of the conductive coating disposed on a conducting ferromagnetic basis, using the phase method of eddy current testing. The reason of the error is variation of the electrical conductivity of the material of coating.Determination of the error is based on calculations using known analytical expressions for the loop with current of sinusoidal form arranged over the infinite half space with a covering as a thin layer. Selected in calculating electromagnetic parameters of coating and substrate approximately correspond to the case -chromium layer on a nickel base. Calculations are performed for different frequencies of current passed through coil.It is shown that at reduction of frequency of the current passes through the coil the error is reduced. The value of the lowest possible operating frequency of the excitation current is determined by the condition of absence influence on the phase introduced into the superimposed transducer emf variations in the thickness of the basis.To reduce the indicated error it is proposed to determine, on the basis of phase method at a relatively high frequency transducer current excitation, conductivity of the material of coating. After this, at a low frequency excitation current and using phase method, the coating thickness is determined, taking into consideration the previously determined value of the conductivity of coating. Also discussed ways to improve the accuracy of phase measurements in the MHz region of the excitation current frequency.